„DRUMURILE BASARABENE” ALE LUI MIHAIL SADOVEANU ÎN ANII DE REGIM SOVIETIC: (Aspecte ale receptării editoriale a creației maestrului)* - POHILĂ, Vlad (BIBLIOPOLIS, 2020)
The author investigates the publication of various works by M. Sadoveanu between 1921 and 2005 in Chișinău. In special are described the editions in Cyrillic, printed in 1951- 1989 - 15 books from the total of 33 works of Sadoveanu editing in the mentioned period. Is highlighting the interest of Sadoveanu for the evolution of language, literature and Romanian culture in Soviet Bessarabia.